THE INFLUENCE OF FAMILY CONDITION, GENDER AND AGE ON THE AGGRESSIVE BEHAVIOUR OF ADOLESCENTS PRONE TO VIOLENT MEDIA IN OGBOMOSO, NIGERIA - F.O. Ojewola (European Scientific Journal, ESJ, 2014)
The effects of media violence is having serious impact on the adolescents overall development of adolescents although it is an indispensable part of their daily living. The study investigated the influence of family condition, gender and age on the aggressive behavior of adolescents that are prone to violent media. Descriptive survey research design was adopted for the study. The target population was made up of all the secondary school adolescents in Ogbomoso zone. Simple random sampling technique was used to select six secondary schools from the forty public secondary schools while two private schools were selected from the twelve viable ones. A total of 400 adolescents were selected for the research study. The Influence of Media Violence on Aggressive Behaviour Questionnaire (IMVABQ) developed by the researcher was administered to the participants. The questionnaire contained twenty – five items with a reliability co-efficient of 0.72. Three null hypotheses were generated and tested at 0.05 alpha level of significant. Descriptive, t-test, ANOVA and Duncan Multiple Range Test (DMRT) were the statistical tools used to analyze the data generated. The major findings indicated that there was a significant difference on the influence of media violence on aggressive behaviour on the basis of family condition. The findings further stated that there was no significant difference on the influence of media violence on aggressive behaviour on the basis of gender. The third hypothesis stated that there was a significant difference on the influence of media violence on aggressive behaviour on the basis of age range. Based on the results of these findings, recommendations were made which include the incorporation of counselling programmes for adolescents to expose them to the evil of violent media programmes.